Middle and High School Students' Opinions, Experiences and Responses Regarding to Cyberbullying - Kalender, Melike Kavuk; Keser, Hafize; Tugun, Vasfi (TURKISH EDUCATION ASSOC, 2019)
The aim of this research is to determine the student's opinion and experience regarding to cyberbullying and to identify the response action pursuant to their involvement to cyberbullying. The working group comprises of 952 students ranging from the age between 11-17. The data was collected in the second term of 2016-2017 academic year. After the finalization of this study, the students' behavior that constitute a cyberbullying, the tools and platforms that were used for cyberbullying and the reasons of being exposed to or conducting cyberbullying were determined. Of the students mentioned-above; 44.5% exposed cyberbullying at least one time, and 22.5% conducted actions that constitute as cyberbullying, and 53.2% became a witness of such actions at least one time. When students exposed to any cyberbullying, their general behaviors are to tell such actions to their parents, friends or teachers at their schools. During the cyberbullying actions, the students indicate that, they have nothing else to do or they will tell such circumstances to their close friends. It was also determined that if any student became the witness of cyberbullying, trying to stop such actions, or helping to the victim of such actions and telling it to adults that have the capacity of provide assistance were the most common behavior.
Keywords: Cyberbullying; Response; Cyber-bully; Cyber-victim; Witness; BULLYING EXPERIENCES; CYBER; PREVALENCE; METAANALYSIS; PERCEPTIONS; ADOLESCENTS; CHALLENGE; VIEWS; Education & Educational Research